Potential Pathogenetic Role of Antimicrobial Peptides Carried by Extracellular Vesicles in an in vitro Psoriatic Model - Capriotti L; Iuliano M; Lande R; Frasca L; Falchi M; Rosa P; Mangino G; Romeo G (Dove Medical Press, 2022)
Lorena Capriotti,1,* Marco Iuliano,1,* Roberto Lande,2 Loredana Frasca,2 Mario Falchi,3 Paolo Rosa,1 Giorgio Mangino,1 Giovanna Romeo1 1Department of Medico-Surgical Sciences and Biotechnologies, Sapienza University of Rome - Polo Pontino, Latina, Italy; 2Pharmacological Research and Experimental Therapy Section, National Center for Drug Research and Evaluation, Istituto Superiore di Sanità, Rome, Italy; 3National AIDS Center, Istituto Superiore di Sanità, Rome, Italy*These authors contributed equally to this workCorrespondence: Giorgio Mangino, Department of Medico-Surgical Sciences and Biotechnologies, Sapienza University of Rome - Polo Pontino, C.so della Repubblica, 79, Latina, 04100, Italy, Tel +39 0773 1757271, Email giorgio.mangino@uniroma1.itPurpose: Extracellular Vesicles (EVs) are a heterogeneous group of cell-derived membranous nanoparticles involved in several physiopathological processes. EVs play a crucial role in the definition of the extracellular microenvironment through the transfer of their cargo. Psoriasis is a prototypical chronic inflammatory disease characterized by several secreted mediators, among which antimicrobial peptides (AMPs) are considered pivotal in the development of the psoriatic inflammatory microenvironment. The role of EVs in the pathogenesis of psoriasis has not been elucidated yet, even if emerging evidence demonstrated that interleukin-17A (IL-17A), the psoriasis-related principal cytokine, modifies EVs release and cargo content. The aim of this work was to analyze whether, besides IL-17A, other psoriasis-related cytokines (ie, IFN-γ, TNF-α, IL-22 and IL-23) could affect EVs release and their AMPs mRNAs cargo as well as to analyze the potential biological effect due to EVs internalization by different acceptor cells.Methods: Nanoparticle tracking analysis (NTA) was performed on supernatants of HaCaT cells stimulated with IL-17A, IFN-γ, TNF-α, IL-22 or IL-23 to enumerate EVs. Real-Time RT-PCR was used for gene expression analysis in cells and EVs. Confocal microscopy and Flow cytometry were used to, respectively, study Netosis and EVs internalization.Results: IL-17A and IFN-γ increased EVs release by HaCaT cells. All the tested cytokines modulated AMPs mRNA expression in parental cells and in their respective EVs. S100A12 and hBD2 mRNAs were upregulated following IL-17A and IL-22 treatments. Interestingly, EVs derived from cytokine treated HaCaT cells induced Netosis in freshly isolated neutrophils. Upregulation of S100A12 and hBD2 mRNA was also detectable in acceptor cells incubated with EVs derived from cells treated with psoriasis-related cytokines.Conclusion: The obtained results highlighted the role of EVs in the composition of psoriasis-associated secretome and microenvironment also suggesting the EV involvement in the spreading of the disease mediators and in the possible associated comorbidities.Keywords: extracellular vesicles, antimicrobial peptides, cytokines, keratinocytes, pathogenesis of psoriasis, comorbidities